Recognizing Mistreatment in Older Adults - Vandeweerd, C.; Firpo, Adolfo; Fulmer, Terry; Paveza, Gregory; Bolton, Marguarette (Handbook of Geriatric Assessment, 2006)
Keywords: Care; Diagnosis; Diseases; Handbooks; manuals; etc; Handbooks; manuals; etc; Older people; Older people; Psychological testing; United States; dept.hhs; faculty_collection

Elder self-neglect and abuse and mortality risk in a community-dwelling population - Dong, XinQi; Simon, Melissa; de Leon, Carlos Mendes; Fulmer, Terry; Beck, Todd; Hebert, Liesi; Dyer, Carmel; Paveza, Gregory; Evans, Denis (JAMA-Journal of the American Medical Association, 2009)
Context Both elder self-neglect and abuse have become increasingly prominent public health issues. The association of either elder self-neglect or abuse with mortality remains unclear. Objective To examine the relationship of elder self-neglect or abuse reported to social services agencies with all-cause mortality among a community-dwelling elderly population. Design, Setting, and Participants Prospective, population-based cohort study (conducted from 1993 to 2005) of residents living in a geographically defined community of 3 adjacent neighborhoods in Chicago, Illinois, who were participating in the Chicago Health and Aging Project (CHAP; a longitudinal, population-based, epidemiological study of residents aged ¿= 65 years). A subset of these participants had suspected elder self-neglect or abuse reported to social services agencies. Main Outcome Measures Mortality ascertained during follow-up and by use of the National Death Index. Cox proportional hazard models were used to assess independent associations of self-neglect or elder abuse reporting with the risk of all-cause mortality using time-varying covariate analyses. Results Of 9318 CHAP participants, 1544 participants were reported for elder self-neglect and 113 participants were reported for elder abuse from 1993 to 2005. All CHAP participants were followed up for a median of 6.9 years (interquartile range, 7.4 years), during which 4306 deaths occurred. In multivariable analyses, reported elder self-neglect was associated with a significantly increased risk of 1-year mortality (hazard ratio [HR], 5.82; 95% confidence interval [CI], 5.20-6.51). Mortality risk was lower but still elevated after 1 year ( HR, 1.88; 95% CI, 1.67-2.14). Reported elder abuse also was associated with significantly increased risk of overall mortality (HR, 1.39; 95% CI, 1.07-1.84). Confirmed elder self-neglect or abuse also was associated with mortality. Increased mortality risks associated with either elder self-neglect or abuse were not restricted to those with the lowest levels of cognitive or physical function. Conclusion Both elder self-neglect and abuse reported to social services agencies were associated with increased risk of mortality. JAMA. 2009; 302(5):517-526 www.jama.com
290 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-145-016-708-660 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Activities of Daily Living; Aged; Aged; 80 and over; Cause of Death; Chicago; Cognition; Elder Abuse; Female; Humans; Male; Mandatory Reporting; Parkinson disease; Proportional Hazards Models; Prospective Studies; Risk; United States; Urban Population; abuse; aged; aging; article; cardiovascular disease; cause of death; cognition; cohort analysis; crime; daily life activity; demography; dept.hhs; diabetes mellitus; educational status; ethnic and racial groups; female; follow up; hazard ratio; hip fracture; human; hypertension; informed consent; longitudinal study; major clinical study; male; mandatory reporting; mortality; neoplasm; outcome assessment; physical activity; population based case control study; priority journal; proportional hazards model; prospective study; public health; research subject; risk; self neglect; social work; socioeconomics; statistics; stroke; urban population

Elder self-neglect: A discussion of a social typology - Paveza, Gregory; Weerd, Carla Vande; Laumann, Edward (Journal of the American Geriatrics Society, 2008)
This article presents a theoretical framework for the study of social and behavioral factors associated with elder self-neglect. The model presented reflects the authors' beliefs that a risk-vulnerability model offers a useful framework from which to study all forms of elder mistreatment, as well as elder self-neglect. This model has particular utility, because it can begin to define the elements of risk and vulnerability that may be addressed using preventative measures as opposed to solely addressing intervention, which is often the case when addressing elder mistreatment and self-neglect. The authors then address a method for using the Consortium for Research in Elder Self-neglect of Texas data as currently constructed and adding to that database to effectively study risks and vulnerabilities in the elder self-neglect population. These additional data would greatly expand the scope of the study. The discussant adds his perspective to the ideas proposed by the authors.
21 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000261064700007
Keywords: Aged; Alzheimer disease; Elder Abuse; Elderly; Geriatric Assessment; Humans; Risk Adjustment; Self-neglect; Social Behavior; Social networks; caregiver burden; cognitive defect; conceptual framework; conference paper; daily life activity; data base; depression; dept.hhs; family violence; functional disease; gerontological research; home environment; human; mental disease; peer-reviewed; preventive health service; self neglect; social aspect; social psychology; social support; substance abuse